Matrix metalloproteinases in cerebrovascular diseases - Fatar, Marc; Stroick, Mark Gregor; Griebe, Martin; Hennerici, Michael G. (Cerebrovascular diseases, 2005)
Matrix metalloproteinases are important factors for tissue remodelling and are activated during several physiological and pathological conditions, including cerebrovascular diseases. We give an overview of the structure, production and physiological effects of these widely distributed proteases and describe the genetic background and regulation pathways. In particular, we discuss the role of matrix metalloproteinases in vascular remodelling concerning ischaemic stroke, brain haemorrhage, vascular dementia, carotid artery plaques and cerebral aneurysms.